PEMBENTUKAN KARAKTER MELALUI SHALAT DHUHA BERJAMAAH DI SD MUHAMMADIYAH BILLINGUAL FULLDAY AL ADZKIYA KABUPATEN WONOSOBO - Fitriyah, Khodijatul; Kamal, Faisal; Mustangin, Akhmad (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2025)
This article aims to analyze character formation through congregational Dhuha prayers at Muhammadiyah Elementary School, Al Adzkiya, Wonosobo Regency. This type of field research is qualitative descriptive at Muhammadiyah Al Adzkiya Elementary School, Wonosobo Regency, with primary data sources consisting of the principal, religious coordinator, homeroom teacher, and students at the school through observation, interviews, and documentation. Data were collected from field notes, interview results, and documentation, then classified into several categories, units, and patterns, and then conclusions were drawn. The findings and analysis show that the habit of performing the Dhuha prayer in congregation has been proven to shape the character of students into a generation that is disciplined, consistent, patient, loves worship, has good morals and is enthusiastic in seeking knowledge. Some students have become accustomed to it both at school and at home, although some are still not accustomed to it. The habit of performing the Dhuha prayer in the formation of religious character is attempted by providing socialization to students about the Dhuha prayer worship which is highly recommended by the Prophet Muhammad, along with its benefits. The habit of performing the Dhuha prayer has implications for providing a sense of calm, concentration and enthusiasm in the classroom so that learning becomes conducive. Students are also accustomed to starting their activities with prayer and supplication, and asking for ease from Allah SWT